Shared Leadership in Self-Managed Team: Individual's Perception - Yong, Ke (2016)
The purpose of this study is to gain in-depth knowledge on how individuals in self-managed teams perceive shared leadership in terms of how they think and feel. This study employs qualitative analysis using semi-structured interview. The key findings of the study is to discover how common shared leadership practice in self-manged teams is and how individuals perceive the leadership style. The concept of shared leadership is being investigated from an individual’s perspective through their past experiences in teams. The advantages and disadvantages of shared leadership are being discussed, followed by the reason why shared leadership practice is not being exercised effectively. In conclusion, these findings have contributed to the implications on managerial study.